Evaluation of the Effect of Five-Finger Shoes on Calf Muscle Electromyography Activity in Novice Runners - Behrouz Hajilou; Elaheh Azadian; Sara Sadeghi; Rounak Mohammadi Sasan (Biyumikānīk-i varzishī)
Objective The foot is the most distal part of the moving human body and serves as the sole point of contact with the ground, transmitting significant forces from the ground to the foot. One of the tools used to modulate these forces during running is appropriate footwear. Therefore, this study aimed to investigate the effect of five-finger shoes on the electromyographic activity of calf muscles in novice male runners while running. Methods In this semi-experimental study, 16 novice runners volunteered to participate. The activity of the anterior tibialis, soleus, and medial and lateral gastrocnemius muscles during the absorption and propulsion phases of running in two conditions—barefoot and using Vibram five-finger shoes—was recorded using an electromyography device. A paired t-test was used for data analysis, with a significance level set at p < 0.05. Results When running with five-finger shoes, the electromyography activity of the anterior tibialis muscle during the absorption phase (p = 0.001) and the soleus (p = 0.002) and medial gastrocnemius (p = 0.010) muscles during the propulsion phase was significantly higher compared to running barefoot. However, the activity of the lateral gastrocnemius muscle did not show a significant difference compared to the barefoot condition (p > 0.05). Conclusion The use of five-finger shoes can be considered a reliable footwear option for sports activities, including running, as the muscle activity during their use is very similar to that during barefoot running.